Effect of Centrifuged Chicken Egg Yolk on the Cryopreservation of Boar Semen - Fuqiang Chang; Biyu Zhang; Haidong Liu; Henglei Fan; Rui Xie; Jing Li; Qianqian Hu; Chongmei Ruan (Animals)
Egg yolk, commonly employed as a cryoprotectant in semen cryopreservation, contains large particle matter that can diminish semen quality post thaw and complicate its quality assessment. For this reason, we designed a centrifugal treatment of chicken egg yolk to evaluate its effect on the cryopreservation of porcine semen. The control group (CG) was prepared with a dilution of chicken egg yolk by conventional mixing treatment, and the experimental group (EG) used a dilution of centrifugally treated chicken egg yolk for the ultra-low-temperature cryopreservation of porcine semen. The freezing process was carried out by conventional freezing methods. The spermatozoa were subsequently assessed for various parameters, including motility, acrosome integrity rate, plasma membrane integrity rate, antioxidant indexes, apoptosis rate, and the expression of apoptosis-related genes. The results showed that, post freeze–thawing, the motility, viability, VSL, and VCL of the spermatozoa in the EG were significantly higher than those observed in the CG (p < 0.05). Additionally, the acrosome integrity and plasma membrane integrity of the spermatozoa in the EG were significantly enhanced compared to the CG (p < 0.05). Furthermore, the EG exhibited significantly lower MDA content and sperm apoptosis rate (p < 0.05), while demonstrating significantly higher T-AOC and CAT levels (p < 0.05) relative to the CG. In comparison to the CG, the EG exhibited a significant reduction in the gene expression of TNF-a and Bax in the spermatozoa (p < 0.05), whereas the expression levels of CAT and Bcl-2 were significantly elevated (p < 0.05). In conclusion, the dilution solution formulated through the centrifugal processing of chicken egg yolk demonstrated efficacy in enhancing the quality of porcine spermatozoa following cryopreservation and subsequent thawing.